Structure Analysis of Journal Article Titles: Systemic Functional Grammar Perspectives - Indrie Harthaty (Budapest International Research and Critics University, 2020)
This article studies about analyzing the nominal group structure of journal article titles based on systemic functional linguistics. Title is important for an article. It tells about the content of the article, so it must effective and accurate. Each writer created titles using different word classes as the components constructing the title, and with different length: short and long structure. The purpose of this study is to identify the components constructing titles in journal articles and to find the dominant component forming them. The method used in this study is qualitative method. In analyzing the data, writer used Systemic Functional Grammar perspectives as SFG provides comprehensive explanation about nominal group. The data were taken from journals published by English Journal Literacy UTama. The study revealed that journal article titles used basic components of nominal group structure and the dominant component constructing the structures was post-modifier functioning as qualifier represented by prepositional phrase.